Kingship and memory in ancient Judah - Wilson, Ian Douglas 1981- (New York, NY Oxford University Press, 2017)
Ancient Judah and its literature: remembering and imagining kingship -- Torah and its guardians -- Cruxes of leadership: the transition(s) to monarchy -- Remembering/forgetting David and Davidic kingship -- The remembered future in prophetic literature -- To conclude: the emplotments of kingship and "metahistoriography" in ancient Judah
"The book had its formal origins in a doctoral dissertation defended at the University of Alberta in March 2015"
Literaturverzeichnis: Seite 235-275
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Criticism, interpretation, etc; Bible -- Criticism, interpretation, etc; Kings and rulers -- Biblical teaching; Jews -- Kings and rulers; Jews -- History -- To 586 B.C; Memory -- Biblical teaching; Bible; Jews; Kings and rulers; Memory; Hochschulschrift